A Study of Motivation Orientations Used from High School to University - Mehdinezhad, Vali (Journal of Education and Vocational Research, 2014)
Learning strategies and motivational orientations are important issues that have attracted the attention of many researchers in recent decades. Thus this research was done with the aim of investigation the use of studentsâ€™ motivational orientations compared with them high school. The type of research is applied, descriptive. Students of University of Sistan and Baluchestan the number of 19750 was considered as target population and with use of Krejcie and Morgan (1970) sample size table 375 students were considered as sample. The main components of motivational orientations were measured with using Taylor-Sims (2011) Motivational Strategies Questionnaire (MSQ). Data was examined with using Paired Sample t-test, Friedman test for prioritize the variables, Analysis Variance and Independentsample t-test. The findings indicated that generally students use less motivational orientation than them high school course and this amount wasnâ€™t desirable. The girls more utilized these skills in comparison with boys. Among different educational groups in just a few components was a significant difference. In rate of using of motivational orientations weren’t significant differences between educational levels and age.